Covid-19 – lessons learned - Mijović, Biljana P (Scripta Medica, 2020)
Modern society has not forgotten yet epidemics that have killed millions in the last millennium, and the COVID 19 pandemic caused by the SARS CoV-2 has emerged. With the onset of the Wuhan epidemic in the Chinese province of Hubei, the initially called a new corona virus due to similarity of 80% to the 2020 SARS virus was renamed to SARS CoV-2. The virus was originally isolated in bronchoalveolar aspirate specimens. In the study, the virus RNK was detected in 6 of 41 blood samples with a clinical signs of infection. A senior Chinese expert told to the media that the median incubation period is 7 days, ranging from 2-12. The International Health Regulations Emergency Committee for epidemics gives a preliminary estimate for R0 of 1.4-2.5. COVID 19 is mainly transmitted by close contact with the infected by drops  due to sneezing and coughing. In a first report of clinical features of infection, the most of patients were presented with fever, cough, myalgia or fatigue. The clinical picture is non-specific. It comes up suddenly exacerbation, bilateral pulmonary which requires admission to intensive care. Initial lethality in hospitalized cases was 15%, but these estimates had to be taken with reserve as the situation evolved. According to recent data, the global fatality rate is 3.7, the lethality rate in China is 3.9% and in Italy 6.8%. According to data from the Chinese Center for Disease Control and Prevention, of 44,672 confirmed cases, 1,023 people died, so letaliett was 2.3%. In the absence of specific prevention and control measures, we are limited to general prevention measures.
Keywords: Covid 19; SARS CoV-2; pandemic; lethality